Gambaran Siklus Hidup Nyamuk Aedes sp. Di Kota Kupang - Yohanes N P Lema; Julianty Almet; Diana Agustiani Wuri (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2021)
Aedes sp. is a type of mosquito that can carry dengue virus which causes dengue fever (DHF). DHF is an increasingly widespread public health problem with the increase in the mobility and population density. One effort that needs to be done in the control of DHF is to cut off the life cycle of mosquito Aedes sp. Therefore, it is necessary to have an understanding of the life cycle of mosquito Aedes sp. This study aims to determine the characteristics of morphology and life cycle of mosquito Aedes sp. in Kupang City. Study location in Kelurahan Oebobo and Kelurahan Kelapa Lima. The selection of this site is based on the highest incidence of DHF according to data from Kupang City Health Office in 2016. The study method includes Aedes sp. mosquito larvae collection, observation of the life cycle and identification of the development of mosquito Aedes sp. include measurement of temperature, humidity and pH of water. Sample of Aedes sp. mosquito larvae collected, then taken to the parasitology laboratory, Faculty of Veterinary Medicine, Nusa Cendana University. Observation of morphological characteristics of mosquito Aedes sp. done in macroscopically and microscopically. Next will observed the life cycle of mosquito Aedes sp. which is carried out at every stage of eggs, larvae, pupa, to adult using a stereo microsocpe and then matched with the identification key. The analytical data used is descriptive analysis shown in the form of table and drawing The results show that the life cycle of mosquito Aedes sp. in Kota Kupang ranging from 7-10 days with details of 1-2 egg stages, 3 days of larvae stage, L4 larvae to pupa 1-2 days and the pupa stage mature for 2-3 days, with an average temperature of 28,3ºC, humidity 60.4% and pH of water 7